Changes in the ultrastructure of cardiac telocytes during early postnatal development of the myocardium of Wistar rats - Zagoruiko , G.E.; Martsinovsky , V.P.; Filatova , V.I.; Matvienko , T.M.; Filatova , O.V.; Sargosh , O.D. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. In 2010, the term "telocyte" was introduced into foreign scientific morphological literature to describe a new type of cell that is part of the connective tissue component of various organs of mammals and humans. Telocytes were found not only in the stromal component of the myocardium of the ventricles and atria, but also in the wall of arterial and venous vessels of the heart of various representatives of mammals and humans. A characteristic feature of the morphology of telocytes, which distinguishes them from other types of cells of vertebrates, is the presence of numerous thin wavy-shaped processes, the length of some of which can exceed 100 microns. Modern morphological studies indicate that the processes of telocytes - telopodia, form homocellular and heterocellular contacts with telocytes and other cells of organs, respectively. Thus, telopodia of telocytes directly contact cardiomyocytes, pericytes, fibroblasts, endothelial cells of blood capillaries, smooth muscle cells of arterioles and venules and nerve endings. It has been established that in the process of contact interaction, signaling molecules are transferred from telopodia of telocytes to other cells. Therefore, the study of telocytes is of great importance for determining the role of these cells in the morphogenesis of cardiac muscle in the process of postnatal development of mammals and humans. Goal. To investigate the features of the ultrastructure and determine changes in cardiac telocytes during early postnatal development of Wistar rats. Methods. Electron microscopic examination of the left ventricular myocardium of late embryos and Wistar rats aged from birth to 45 days of postnatal development was performed. Results and summary. It has been established that single cardiac telocytes “accompany” cardiomyocytes of the left ventricular myocardium in 20-day-old rat embryos. In the myocardium of newborn rats, optically dark and light telocytes with thin long sinuous processes are detected, in which local expansions (podomere) and thin short and long podomeres are detected. On the 10th day after the birth of rats, an increase in the number of postmitotic young cardiac telocytes, which have a triangular and rhombic shape, is determined in the myocardium. The peripheral parts of the body of these telocytes end in thin short slightly sinuous dichotomously branched processes. In the myocardium of 15-day-old rats, the number and length of sinuous processes of telocytes significantly increase. In the time interval (20 - 45) days, the content of cardiac telocytes in the rat myocardium gradually decreases. Thin podomeres form homocellular and heterocellular contacts, which suggests the influence of cardiac telocytes on the morpho-functional state of cardiomyocytes and cells of the stromal-vascular component of the myocardium.